The effects of AMPA blockade on the spectral profile of human early visual cortex recordings studied with non-invasive MEG. (August 2016) - Muthukumaraswamy, Suresh D.; Routley, Bethany; Droog, Wouter; Singh, Krish D.; Hamandi, Khalid
Abstract: The generation of gamma-band (>30 Hz) cortical activity is thought to depend on the reciprocal connections of excitatory glutamatergic principal cells with inhibitory GABAergic interneurons. Both in vitro and in vivo animal studies have shown that blockade of glutamatergic α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid (AMPA) receptors reduces the amplitude of gamma-band activity. In this registered report, we hypothesised that similar effects would be observed in humans following administration of perampanel, a first in class AMPA antagonist, used in the treatment of epilepsy. In a single-blind placebo-controlled crossover study, 20 healthy male participants completed two study days. On one day participants were given a 6 mg dose of perampanel and on the other an inactive placebo. magnetoencephalography (MEG) recordings of brain activity were taken before and two hours after drug administration, with activity in the visual cortex probed using a stimulation protocol known to induce gamma-band activity in the primary visual cortex. As hypothesised, our results indicated a decrease in gamma-band amplitudes following perampanel administration. The decreases in gamma-band amplitudes observed were temporally restricted to the early time-period of stimulus presentation (up to 400 msec) with no significant effects observed on early evoked responses or alpha rhythms. This suggests that the early time-window of induced visual gamma-band activity, thought to reflect input to the visual cortex from the lateral geniculate nucleus, is most sensitive to AMPA blocking drugs.